Post-Injection Delirium/Sedation Syndrome: A Case Report and 2-Year Follow-Up - Podgorná, Gabriela; Albrecht, Jakub; Buday, Jozef; Mareš, Tadeáš; Le, Thai Hong; Kališová, Lucie; Anders, Martin (The american journal of case reports, 2022)
BACKGROUND Long-acting injectable (LAI) antipsychotics are one of the forms of therapy for severe mental illness. Post-injection delirium/sedation syndrome (PDSS) is a very rare but serious adverse effect following the application of an olanzapine in a long-acting form. The most common symptoms of the syndrome are sedation, delirium, dysarthria, ataxia, extrapyramidal symptoms, agitation, dizziness, or seizure. The predispositions, prevention, and exact mechanism of PDSS remain unclear. CASE REPORT We present a case report of a 30-year-old male patient experiencing PDSS, including the main symptoms of PDSS, diagnostic methods, olanzapine plasma concentrations, therapeutic process, and outcome. We then include a follow-up of the patient 2.5 years later. The patient did not have any long-term damage, had no disabilities, and no post-traumatic stress disorder following the event. We include information about his current medications, further use of LAI antipsychotics, and update about his everyday life. CONCLUSIONS PDSS is a life-threatening condition clinicians must be aware of, and the easiest precaution is a 3-h observation after the application of an injection. Because the predispositions, prevention, and exact mechanism of PDSS remains unclear, it is very important to report the rare cases of PDSS and conduct further research for the safety of our patients. The follow-up of the patient showed that the patient is doing well, he has no post-traumatic stress disorder following the event, and he did continue to use LAI antipsychotic medication.
Keywords: Olanzapine; Humans; Delayed-Action Preparations; následné studie; olanzapin; dospělí; lidé; Adult; benzodiazepiny; antipsychotika; Male; delirium; Delirium; Benzodiazepines; léky s prodlouženým účinkem; Injections, Intramuscular; Antipsychotic Agents; mužské pohlaví; injekce intramuskulární; Follow-Up Studies